A DANÇA DE SÃO GONÇALO EM RIO AZUL-PR: UMA LEITURA A PARTIR DA FILOSOFIA TRÁGICA DO JOVEM NIETZSCHE - Gapinski, Ivan (2014)
The purpose of this dissertation is to do a study on the São Gonçalo`s dance in the municipal district of Rio Azul PR, tends a backdrop the tragic conception of the present existence of the youth`s of the German philosopher writings of Fridrich W. Nietzsche (1844-1900). Through the nietzschean interpretation of Greek Tragedy and other texts of the first period of his production, it is looked for to understand in that measured the dance created by the Portuguese priest Gonçalo de Amarante in the thirteenth century - with the intent of converting prostitutes, and it was danced inside of the Churches when it arrived in Brazil amid the settler`s cultural luggage - it can be conceived as indication of a tragic vision of world. This danced devotion suffered persecutions and prohibitions so much of the Portuguese state as of the Catholic church, both saw in her some excess and traces of a paganism that wanted to extirpate of the Christian doctrine. Though, the dance persisted and it is found still in places where the ecclesiastical surveillance didn`t achieve success, as in the communities of the interior of Brazil. She also found in some communities of Rio Azul PR as payment promise by grace received. This dance is accompanied by guitars, violas and singings, and displays a cheerful form of expressing the religiosity and of conceiving the life. Known among the residents of the area as Pilgrimage of São Gonçalo is understood with a tragic ritual because in it there is the reconciliation although momentary among elements had as antagonistic, but at the same time complementally and necessary each other, such as life and death, sacred and profane, as well as they were Apollo and Dionisio in the Greek tragedy, considered by Nietzsche in his youth as the supreme art of the existence. The used methodology was the analysis of despoilments collected from residents of some places of Rio Azul and adjacent municipal districts that participate or they participated in the called Pilgrimages of São Gonçalo, in contrast to the historical study on the Portuguese saint and his sacred dance, to the light the nietzschean interpretation of Greek tragedy.